Economic implications of the Regional Comprehensive Economic Partnership for Asia and the Pacific - Cyn-Young Park; Peter A. Petri; Michael G. Plummer (Asian Development Bank (ADB), 2021)
The Regional Comprehensive Economic Partnership (RCEP) presents strong potential to mold regional trade and investment patterns well into the future and to influence the direction of global economic cooperation at a challenging time. This paper evaluates the RCEP and estimates its potential effects on income, trade, economic structure, factor returns, and employment using a computable general equilibrium model. The results suggest that the RCEP agreement could generate global income gains that will be almost twice as large as those of the Comprehensive and Progressive Agreement on Trans-Pacific Partnership (CPTPP). RCEP effects on the region's trade will also significantly deepen regional production networks and raise productivity. At the sectoral level, exports and imports of nondurable and durable manufactures will experience the most growth. The CPTPP and RCEP will especially strengthen the region's manufacturing supply chains, increasing wages and employment.
Keywords: F13; F15; F17; 330; computable general equilibrium; Comprehensive and Progressive Agreement on Trans-Pacific Partnership; free trade agreement; Regional Comprehensive Economic Partnership; rules of origin; supply chains